Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

How do you solve 2x(x+3)=(x+1)(2x-5)

Sagot :

distribute and get 2x^2+6x=2x^2+2x-5x-5
add like terms and get 2x^2+6x=2x^2-3x-5
subtract 2x^2 from both sides and get
6x=3x-5
subtract 3x from both sides
3x=5
divide both sides by 3
x=5/3